ANALISIS EKOLINGUISTIK DALAM BUKU TEKS BAHASA INDONESIA SISWA KELAS VII SMP/MTS EDISI REVISI - Ayyu Subhi Farahiba; Kisyani Laksono; Didik Nurhadi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This study aims to analyze environmental-themed discourse and ecolexicon forms in the Revised Edition of the Indonesian Language Textbook for grade VII students of junior high schools/Islamic junior high schools. Through an ecolinguistic approach, this study explores the use of language in texts to represent environmental issues. Data were taken from textbooks published by the Ministry of Education and Culture in 2023. This study uses a descriptive analytical method with documentation, listening, and note-taking techniques, as well as interactive data analysis. The results of the study show that environmental-themed discourse in the Indonesian Language Textbook Revised Edition in 2023 is dominated by discourse in the form of news texts. Ecolexicons in environmental discourse are manifested in the form of words and phrases. The diversity of these themes has the potential to increase students' awareness of environmental issues. However, the findings also show that the presentation of environmental-themed discourse is still lacking, so further efforts are needed to integrate ecological values ​​​​in textbooks in order to build students' ecological intelligence.